An Investigation into the Factors that Militate Against Recently Trained Teachers Implementing New Ideas - Spencer, W. Anthony.A (2009)
The purpose of this study was to determine some of the factors that affect the performance of newly trained teachers in Antigua and Barbuda and to also determine the perceptions of these teachers on their actual performance. The literature review suggested that several factors including the school climate, school leadership and the teacher as a unique individual, can significantly impact the performance of the newly trained teachers. This mixed methods study involved the use of structured interviews and a questionnaire survey and the findings suggest that, indeed, many new teachers feel hampered by inadequate preparation, insufficient support by colleagues and school leadership and also by lack of ready access to physical resources.